It took a pandemic: Enduring lessons for improving accessibility in medical education. Issue 11 (2nd May 2022) - Wallon, Robert C.; Gossett, Jennifer; Meeks, Lisa M.
Abstract : In March of 2020, the rapid onset of the COVID‐19 pandemic halted the gears of undergraduate medical education programs in the U.S. and in many locations across the globe. Disruptions to usual practice provided the impetus for educators to creatively re‐envision medical education with approaches that shared a common feature: flexibility. Out of the chaos of the pandemic rose a collective willingness to think creatively and adapt ( see https://bit.ly/3x91Y8H ). Although this type of creativity had been used prior to the pandemic to develop accommodations for individual students with disabilities, these changes occurred on a larger scale and increased flexibility for entire cohorts and programs.